Knowledge of mothers from low & middle income families in selected cities in Metro Manila on the use and donation of human milk banks - Berroya, James Roi A.; Carreon, Rald Shenda Z.; Esquivel, Samantha Christine F.; Rosales, Julia Mishael M.; Bayaga Celile Leah T., RND, PhD. (Quezon City University of the Philippines Diliman, 2023)
Human milk banks (HMBs) play a pivotal role in neonatal care by ensuring that infants receive continued optimum nutrition during this critical time of growth and development. This study aimed to determine the knowledge of non-pregnant and non-lactating mothers from low- and middle-income families in Metro Manila on the use and donation of human milk in human milk banks as well as determine the knowledge of those with and without peer or family support. A qualitative descriptive design was used wherein open-ended, semi-structured interviews were conducted to determine the knowledge of 32 non-lactating, and non-pregnant mothers from both income classes. The data obtained underwent thematic analysis and common themes were compared to identify commonalities and differences between income classes. Key themes identified in the knowledge of mothers on the use and donation of DHM from HMBs were the superior nutritional value of breast milk and the purpose of HMBs to cater to mothers unable to produce breast milk as well as sick and preterm infants. Moreover, mothers identified the safety of DHM from HMBs due to screening and storage procedures. However, 72% of participants did not know the existence of HMBs in Metro Manila. The study also found that low-income mothers were less knowledgeable about the specific benefits of breast milk compared to middle-income mothers. Conversely, low-income mothers were more familiar with the specific screening and storage procedures to ensure the safety of DHM compared to middle-income mothers. Family and peers of low-income mothers were also more supportive of using and donating DHM from HMBs. The study concludes that the promotion of HMBs in the Philippines needs to be strengthened. Future studies could evaluate existing programs and initiatives of HMBs in the Philippines to address the gaps in the knowledge of mothers and to further the findings of this study.
Thesis
Includes bibliographical references (pages 120-145)
Keywords: Breast milk -- Philippines -- Metro Manila; Breast milk -- Collection and preservation -- Philippines -- Metro Manila; Mothers -- Philippines -- Metro Manila